2013
DOI: 10.2147/ndt.s45402
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dorsolateral prefrontal cortical hemodynamic response in adult obsessive-compulsive disorder as measured by near-infrared spectroscopy during the verbal fluency task

Abstract: BackgroundNear-infrared spectroscopy has helped our understanding of the neurobiological mechanisms of psychiatric disorders and has advantages including noninvasiveness, lower cost, and ease of use compared with other imaging techniques, like functional magnetic resonance imaging. The verbal fluency task is the most common and well established task used to assess cognitive activation during near-infrared spectroscopy. Recent functional neuroimaging studies have shown that the orbitofrontal cortex and other br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…The present result is consistent with the results of previous NIRS studies that patients with OCD showed decreased prefrontal hemodynamic responses [ 13 , 14 ]. In this patient with OCD, SSRI treatment with exposure therapy was symptomatically effective, and NIRS findings showed improvement of brain function in the temporal and frontal lobes after treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The present result is consistent with the results of previous NIRS studies that patients with OCD showed decreased prefrontal hemodynamic responses [ 13 , 14 ]. In this patient with OCD, SSRI treatment with exposure therapy was symptomatically effective, and NIRS findings showed improvement of brain function in the temporal and frontal lobes after treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, although the electrophysiological literature is sparse, both EEG and MEG data support other functional imaging modalities (Beucke et al 2013; [104] in their implication of elements of a frontocortical, striatal, thalamic circuit with involvement of limbic regions, in line with current neural model of OCD [105].…”
Section: Electroencephalography (Eeg) and Magnetoencephalography (Meg)supporting
confidence: 67%
“…Separate brain regions and signaling pathways influencing compulsive-like and anxiety-like symptoms are most likely the explanation for the observed lack of a dFBr effect in the OF test. Anxiety is attributed primarily to the amygdala and ventral hippocampus (McHugh et al, 2004), whereas compulsions and obsessions have been linked to dorsolateral prefrontal cortex (Hirosawa et al, 2013), anterior cingulate cortex (Fitzgerald et al, 2005), orbitofrontal cortex (Beucke et al, 2013) and dysregulation of the corticostriatal-thalamo-cortical circuitry (CSTC; Ting and Feng, 2011). These regions receive projections from the amygdala and hippocampus (McDonald, 1991; Eblen and Graybiel, 1995; Welch et al, 2007; Toyoda et al, 2011; Chen and Etkin, 2013) explaining the co-existence of anxiety along with OCD, which appears to be specific to anxiety related to compulsive-like behaviors rather than more generalized anxiety.…”
Section: Discussionmentioning
confidence: 99%